Incidence and clinical presentation of groin injuries in sub-elite male soccer - Hölmich, P.; Thorborg, K.; Dehlendorff, C.; Krogsgaard, K.; Gluud, C. (British Journal of Sports Medicine, 2014)
Background: Groin injuries cause major problems in the football codes, as they are prevalent and lead to prolonged symptoms and high recurrence. The aim of the present study was to describe the occurrence and clinical presentation of groin injuries in a large cohort of sub-elite soccer players during a season.